Base-Promoted, Mild and Highly Efficient Conversion of Arylboronic Acids into Phenols with tert-Butyl Hydroperoxide - Guo, Shengmei; Lu, Lin; Cai, Hu (Synlett, 2013)
A mild and efficient protocol for the synthesis of phenols from arylboronic acids has been developed by using tert-butyl hydroperoxide with base as promoter. The corresponding phenols were obtained in good to excellent yields within several minutes.
Keywords: arylboronic acid; phenol; peroxides; base; synthetic methods